Is Theory of Translation Needed to Build Students’ Translation Competence? - Havid Ardi (International Conference on Languages and Arts, 2012)
This article presents the importance theory of translation in translation training to build translation competence in revitalizing the teaching of translation. Firstly, the translation competence is defined. Then, six sub-competences of translation competence are described and materials given in the translation subject to build students’ competence are presented. This competence builds students’ awareness in detecting translation problem and finding the strategy to solve it. Some strategy applied by the translator in his translation (translation technique) are presented. These techniques are implemented to solve untranslatability. By introducing these techniques, the students improve their translation competence, especially in translating untranslatable words or expression. Students’ responses on the materials related the translation theory are also presented. This will be useful input for future improvement for the translation subject.Key words: translation theory, translation competence, problem-based solving